Toxic Effect of Heavy Metal, Cadmium Concentration in Baraila Lake Fish Water Channa Punctatus - Anand, Renu; Kumar, Vijay (American Journal of Biology and Natural Sciences, 2025)
Pesticides are synthetic chemical used for pest control. A major source of pesticides in water bodies is the runoff from agricultural fields. Some pesticides also enter inland waters from industries, which use pesticides in their manufacturing processes or from the manufacturing of pesticides themselves. Pesticides adversely affect a wide range of organismes including insects and fish. Pesticides accumulate in the tissues of aquatic organisms through bio concentration and biological magnification and adversely affect their metabolic processes including reproduction. The experimental fish sub lethal concentration of Cadmium chloride caused various behavioral abnormalities in fish such as an erratic increased swimming, surfacing and hyperactivity, restlessness, abnormal swimming, and secretion of mucous which was followed by loss of balance and succumbing of fish, when they are initially exposed to cadmium chloride test solution. Throughout the exposure period the fishes showed various aggressive behavior abnormalities such as nudge and nip, fin flickering, partial and S-jerk and burst swimming increased significantly (P<0.05) compared with control. It is also observed that the aforementioned responses are significantly and gradually. The sublethal concentration of Cadmium chloride caused changes in various behavioural and haematological indices of Channa punctatus, including the accumulation of blush white mucous-like substance clogged on the vital external areas of the fish skin. These deposits were suspected to be salts of cadmium. They were noticed only in the Cd treated fishes, which indicated contamination through water.